Prognostic relevance of cathepsin D detection in micrometastatic cells in the bone marrow of patients with primary breast cancer - Solomayer, Erich-Franz; Diel, Ingo J.; Meyberg-Solomayer, Gabriele Christine; Gollan, Christina; Bode, Simone; Wallwiener, Diethelm; Bastert, Gunther (Breast cancer research and treatment, 1998)
Patients with an elevated level of cathepsin D in breast cancer tissue have an adverse prognosis. This study evaluated the prognostic relevance of cathepsin D detection in disseminated tumour cells in bone marrow. Bone marrow was sampled intraoperatively from both anterior iliac crests in 290 patients with primary breast cancer. Interphase cells were enhanced and stained immunocytologically with two antibodies: BM2, which detects tumour-associated glycoprotein TAG 12, which is typically expressed by almost all breast cancer cells, and the anti-cathepsin D antibody. 67 of 149 BM2-positive women (45%) developed metastatic disease (median follow-up time: 69 months). Of these, 15 were cathepsin D-positive (22%). Patients with cathepsin D-positive cells in bone marrow (n = 26; 9%) had a significantly shorter metastasis-free interval (38 months) compared with women who were cathepsin D-negative (64.5 months). The worst prognosis was seen in patients positive for both markers (30.5 months), followed by those who were cathepsin D-negative and BM2-positive (48 months). The detection of cathepsin D on disseminated tumour cells characterises a subgroup of patients with a poorer prognosis who should undergo more aggressive adjuvant systemic therapy.